CIGARETTE SALES DATA FOR REFINERIES SYSTEM USING FOXPRO APPLICATION ON GARUDA STORE - Nori Ansari; Eko Hadiyanto, SSi, MMSI (Jurnal Sistem Informasi, 2003)
The role of computers on the computerized sales system with the use of cigarettes in stores Garuda FoxPro application has many advantages compared with the previous manual system. Can easily provide the necessary information on matters relating to the sale of Morocco, reduce errors in routine work and time efficiency of very bergarga for the progress of the company.